Naeruga teritatud pliiats: huumor kui vabadus õdede Meide loomingus [A pencil sharpened by laughter: humor as freedom in the work of the Mei sisters] - Stahl, Kai; Taavet, Ave; Voolaid, Piret (Estonian Literary Museum Scholarly Press, 2026)
From 14 March to 31 August an exhibition entitled “The Mei Sisters: Avant-garde and Ordinary Life” was mounted at KUMU, the Estonian Museum of Art. In the last hours before it closed, it was possible to enjoy the exhibition with the competent guidance of curators Ulrika Jõemägi and Kai Stahl. Also, at the initiation of folklorist Piret Voolaid, a panel discussion took place entitled “A Pencil Sharpened by Laughter: Humour as freedom in the works of the Mei Sisters”, which included curators Eha Komissarov and Kai Stahl and the ani- mator, writer and caricaturist Ave Taavet.